Entrepreneurship and technology policy - Link, Albert N. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2006)
This book is divided into four parts: Government's Direct Support of R&D, Government's Leveraging of R&D, Government's infrastructure Policies, and Knowledge Flows from Universities and Laboratories. Most of the journal articles are relatively new, being published since the mid-to late-1990s, but these key articles represent what could become the cornerstone for all future research related to entrepreneurship and technology policy.
Includes bibliographical references and index.
gau 21/05/14
Loans
Keywords: Entrepreneurship; Technology and state